Analisis Faktor Penyebab Kerusakan Dan Perbaikan Jalan Raya Balongbendo Sta 34 + 000 – Sta 39 + 000 Kabupaten Sidoarjo Menggunakan Metode Bina Marga - Nuril Fikri; Nurani Hartatik; Laily Endah Fatmawati (Journal on Education, 2024)
This research is motivated by types of road damage, index values ​​and solutions to repair damage that occurs on Jalan Raya Balongbendo. The aim of this research is to identify types of damage, calculate index values, and analyze solutions in repairing damage that occurs on Jalan Raya Balongbendo. The method in this research is Bina Marga 1990 by collecting data from location survey results and secondary data. The research results showed that the types of damage that occurred on Jalan Raya Balongbendo were Edge Cracks, Crocodile Skin Cracks, Holes and Patches. From the calculation data obtained based on the road condition values, a periodic maintenance and routine maintenance program was taken.